(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2021)
This assessed influence of school location implementation of secondary schools Physical Education curriculum in Nigeria. To achieve this purpose, purposive sampling technique was used to select the samples from the Six Geo- political zones of the country. The population for the study was all secondary schools of Fifty Four thousand Five hundred and twenty- one (54,521) with sample size of Six hundred and Fifty six (656). The data collected were statistically analysed using descriptive statistics of mean (x) and standard deviation (sd) to test and analysed bio- data variables and to answer research questions: while inferential statistics of One Sample t- testwas used to test all the hypothesis. The major findings from the study revealed that school location influence implementation of secondary schools Physical Education curriculum in Nigeria. The study recommended that school should be located or cited in an area where space is available as subject like Physical Education requires large space of land where students could put theory into practice.